(untitled) (Comprehensive Journal of Science, 2026)
This paper examines British colonial policy in Libya (1943–1952) and its role in the internationalization of the Libyan question after World War II, as well as Britain’s efforts to exert its influence, particularly through the adoption of a federal system. It also addresses British administrative and political methods and international maneuvering, highlighting the impact of these policies on the establishment of the Libyan state and the continued influence of major powers on Libyan affairs.